Penerapan Backpropagation Neural Network (BPNN) Untuk Prediksi Kecanduan Smartphone Pada Remaja - Mochammad Anshori; M. Syauqi Haris; Wahyu Teja Kusuma (UNIVERSITAS RAHARJA, 2023)
COVID-19 caused by the coronavirus disease-2019 has spread rapidly and attacked massively. As a precaution, a lockdown policy was issued. This policy limits the activities of schools, offices, shops, prohibits traveling at certain times, maintains distance from one another and reduces crowds in the public. During the lockdown period resulted in a new lifestyle where the use of smartphones increased. This increase is based on the fact that smartphones have many functions such as information, communication, education and entertainment. But excessive use of smartphones can cause addictive effects, especially in adolescents. Excessive use of smartphones makes teenagers become insomniac, different social behavior, low self-confidence, and even anxiety. The complexity of anxiety symptoms in adolescents tends to be difficult to understand, therefore a prediction of smartphone addiction with backpropagation is proposed. Parameter testing is done to get the right artificial neural network architecture. The results of testing the parameters that have been carried out are iterations = 50, the number of neurons in the hidden layer = 9 and the learning rate = 0.3. With this model, an accuracy of 99.49%, TPR of 99.5% and FPR of 0.08% is obtained. Keywords—Backpropagation, Artificial Neural Network, Smartphone Addiction, Machine Learning, Neural Network COVID-19 yang disebabkan oleh coronavirus disease-2019 telah menyebar dengan cepat dan menyerang secara masif. Sebagai tindakan pencegahan maka dikeluarkan kebijakan lockdown. Kebijakan ini membatasi kegiatan sekolah, perkantoran, pertokoan, melarang bepergian dalam waktu tertentu, saling menjaga jarak dan mengurangi kerumunan di publik. Selama masa lockdown menghasilkan gaya hidup yang baru dimana kegunaan smartphone meningkat. Peningkatan ini didasari karena smartphone memiliki banyak fungsi seperti informasi, komunikasi, edukasi dan hiburan. Tetapi penggunaan smartphone yang berlebihan dapat menimbulkan efek candu khususnya pada remaja. Berlebihan dalam menggunakan smartphone membuat anak remaja menjadi insomnia, Tingkah laku pergaulan yang berbeda, kepercayaan diri yang rendah, bahkan kecemasan. Kompleksnya gejala kecemasan pada anak remaja cenderung sulit untuk dipahami, oleh karena itu diusulkan prediksi kecanduan smartphone dengan backpropagation. Pengujian parameter dilakukan untuk mendapatkan arsitektur jaringan syaraf tiruan yang tepat. Hasil pengujian parameter yang telah dilakukan adalah iterasi = 50, jumlah neuron pada hidden layer = 9 dan nilai learning rate = 0.3. Dengan model tersebut, maka didapatkan akurasi sebesar 99.49%, TPR sebesar 99.5% dan FPR sebesar 0.08%. Kata Kunci—Backpropagation, Jaringan Saraf Tiruan, Kecanduan Smartphone, Pembelajaran Mesin, Jaringan Saraf